The effects of differentiated music exposure on 10-km cycling time trial - Lim, H.; Karageorghis, C. I.; Bishop, D. T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Researchers investigating the effects of asynchronous music in sport and exercise typically employ music for the entire duration of the activity. The few studies that had manipulated the exposure of asynchronous music in-task have reported improvements in psychological state and work output (e.g., Lim et al., 2009, Lima-Silva et al., 2012). The aim of the present study was to investigate the effects of differentiated asynchronous music exposure on a 10-km cycling time trial. Methods: After completing a familiarization trial, 24 Caucasian males were administered four 10-km time trials in a counterbalanced order: No-music control (C); music throughout the trial (M1); music played from 0-5 km (M2); and music played from 5-10 km (M3). A repeated measures ANOVA was carried out to analyse time to completion, speed, cadence, heart rate, RPE, affect and arousal. Results: Significant interactions (p < .05) were observed for all dependent variables with the exception of time to completion and RPE, while significant main effects (p < .05) were reported for time to completion, speed, heart rate and arousal. There were also significant distance effects for all dependent variables (p < .05). Follow-up pairwise comparisons indicated that trials were significantly faster under M1 (Mtime to completion = -43.42, Mspeed = 1.13, Mheart rate = 7.82) and M3 (Mtime to completion = -26.54, Mspeed = .64, Mheart rate = 4.56) when compared to control, while M2 did not significantly differ (p > .05) when compared against the other three conditions. Discussion: Participants generally cycled faster with asynchronous music compared to a no-music control, suggesting the presence of energy reserves (Crewe et al., 2004). These faster times with associated with higher heart rates, though the increase in physiological demand did not correspond with an increase in RPE. This indicates that cycling to asynchronous music enabled participants to achieve superior physical performance without a concomitant increase in conscious effort, in line with the parallel processing theory (Rejeski, 1985). Affective valence was positively influenced only when music was presented in the second half of the time trial, suggesting that the point of exposure is a critical factor to consider in the application of music. Further research is required to investigate the reasons behind this phenomenon.